Leadership of The Principal In Improving Teacher Performance at SDN 12 Rambang - Aini Darmasita (International Journal of Educational Review, 2022)
This article aims to reveal about how the principal's leadership in improving teacher performance at the State Elementary School 12 Rambang. This type of research is qualitative research. The subjects of this study were 12 teachers. The data analysis technique used is descriptive analysis technique. Data collection techniques used are interviews and documentation. The findings show that the principal's leadership is good. This can be seen from the principal who motivates teachers, giving warnings to teachers who are less disciplined. And the teacher's performance has been good, judging from the good teacher administration, such as the implementation of learning plans, the use of learning methods according to the material.